Pengaruh Penambahan Puree Kecipir (Pshophocarpus tetragonolobus L.) Terhadap Karakteristik Bakso Ayam - Lucia, Marcelyna; Timur Ina, Putu; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
This research was aimed to determine the effect of winged bean puree additions on the characteristic of chicken meatball and to find out the best additions winged bean puree to produce chicken meatball with the best characteristics. The experimental design used in this research was a Completely Randomized Design (CRD) with a additional of winged bean puree consisting of 5 treatments namely: 0%; 10%; 20%; 30%; 40%. The treatment was repeated 3 times so that they were obtained 15 experimental units. The data obtained were analyzed by variance and if the treatment had a significant effect on the treatment, then followed by Duncan’s Multiple Range Test (DMRT). The results showed that the addition of winged bean puree had a significant effect on moisture content, ash content, protein content, crude fiber content, hedonic test (color, aroma, taste, texture and overall acceptance) and scoring test (taste and texture). The addition 40% concentration of winged bean puree resulted the best characteristics with moisture content 68.00%, ash content 2.05%, protein content 14.40%, crude fiber 4.87%, level of elasticity 4.49 N, color was liked, aroma was liked, very typical taste of winged bean and liked, chewy texture and liked, and overall acceptance was liked.